Persepsi mahasiswa terhadap perkembangan pendidikan vokasi di program pendidikan teknik mesin - Nyenyep Sriwardani (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2011)
THE PERCEPTION OF STUDENTS ON THE DEVELOPMENT OF VOCATIONAL EDUCATION IN MECHANICAL ENGINEERING EDUCATION PROGRAMSVocation education or educationfor life and education for earning living is an option to determine a future. Vocation education conceptually focused on education adjusting to the demand driven, link and match between the employee with the employer. While success is measured by the number of education graduates and the suitability of the absorption area of work with a practiced expertise. Vocation education system serves the political, economic, social, art and so on. For a number of Indonesian workers productive enough, and have the ability to adapt imported technologies to the characteristics of the skill intensive quality improvement and implementation of education advocacy was the main focus should be. In this study we tried to describing the data to determine student perceptions of PTM to the development of vocation education. From this it can be seen that there are still some students who do not understand the vocation education and there are several roles and functions of teachers who are not perceived by the students benefit. This phenomenon can be anticipated with the provision of guidance and motivation to the students more intensively, and increased educational facilities are more adequate to be more intensive faculty in also appreciate themselves.